Microplastics (MPs) in urban roadside snowbanks: Quantities, size fractions and dynamics of release - Vijayan, Arya; Österlund, Heléne; Magnusson, Kerstin; Marsalek, Jiri; Viklander, Maria (Science of The Total Environment, 2022)
The microplastics (MP) pollution has been receiving high attention in recent years, because of the massive amounts of plastics it contributes to the environment. Tyre wear and road wear particles (TWP and RWPs) were identified as major sources of MPs, but the observed data on these particles in urban snow deposits and snowmelt is scarce. To contribute to remediation of this situation, a study designed to quantify TWPs and RWPs in urban roadside snowbanks, and assess the MP occurrence in three size fractions, was conducted in the Luleå and Umeå municipalities in Northern Sweden. TWPs and RWPs were determined in three size fractions: 50–100 μm, 100–300 μm, and ≥300 μm, and their release from melting snow was investigated in the laboratory under controlled conditions. Among the MPs identified in snow and the associated snowmelt samples, a majority consisted of both types of particles (T&RWPs) with an average of 20,000 ± 48,000 number/L, whereas other MPs (fibres, fragments, flakes, and films of plastic) were much less plentiful with an average concentration of 24 ± 16 number/L. The largest proportion of T&RWPs was detected in the size fraction 50–100 μm (around 80 %), and the smallest proportion was in the fraction ≥300 μm (about 2 %). Of the T&RWPs, about 85 % were black bitumen particles (RWPs), composed of bitumen, mineral material and polymer modifiers, and 15 % were tire wear particles (TWPs) composed of rubber. The laboratory snow melting experiments demonstrated that urban snow stored MPs, which were eventually released during snowmelt. The ultimate fate of released MPs would depend on snowmelt drainage; it may either drain away from the road pavement and infiltrate into the ground, or enter the road gutter and be conveyed to storm sewers discharging to the receiving waters. Validerad;2022;Nivå 2;2022-09-05 (hanlid)